Perencanaan Pondok Pesantren Darul Qur’an dalam Meningkatkan Kualitas Hafalan Santri di Kabupaten Sumedang - Putri Koswara, Riska; Setiawan, Asep Iwan; Silvyana, Zaura (Tadbir: Jurnal Manajemen Dakwah, 2025)
The study aims to determine the planning process of Islamic Boarding Schools in improving the quality of students' memorization, including the planning process, programs, and results of the programs implemented. The method used in this study is descriptive qualitative. Based on research on planning at Islamic Boarding Schools, data was obtained that: (1) the planning process is carried out in several stages, namely determining program targets, determining memorization methods and strategies, selecting teaching staff, determining memorization targets, and conducting evaluations; (2) programs at the Islamic Boarding School Ulumul Qur'an which are the focus of the study; (3) the results of the programs implemented with increasing the quality of students